AKTIVITAS ANTIBAKTERI DAN KOMPONEN KIMIA MINYAK ATSIRI TEMU KUNCI (Boesenbergia rotunda L. Mansf) TERHADAP BAKTERI PENYEBAB JERAWAT - Mulyaningsih, Sri; Anastasya, Yolanda; Darmawan, Endang (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Essential oil of fingerroot (Boesenbergia rotunda L. (Mansf)) have antibacterial activity against Staphylococcus but was not specific against acne-causing bacteria. The aim of this study was to determine its chemical content and antibacterial activity of the fingerroot oil against S. aureus, S. epidermidis, and Propionibacterium acnes that cause acne. The essential oil was isolated by steam and water distillation. The organoleptic, yield, and refractive index were observed. Gas chromatography-mass spectrometry (GC-MS) carried out the identification of essential oil components. Antibacterial activity of the oil was determined with the diffusion method. Broth microdilution methods was used for determination of the minimum inhibitory concentration (MIC) and minimum bactericide concentration (MBC). Fingerroot essential oil was clear in color, aromatic odor, chelate taste, and slightly bitter with a yield of 1.19%. The refractive index was 1.4785 ± 0.0001. GC-MS identification showed 5 main components of fingerroot oil were camphor (28.70%), ocimene (24.71%), eucalyptol (16.26%), geraniol (14.81%), and methyl cinnamate (4.16%). The diameter of the zone of inhibition of bacterial growth was greatest at 20% concentration of fingerroot oil, followed by 10%, 5%, and 2.5%. MIC value of fingerroot oil against S. aureus and S. epidermidis was 0.625% and against P. acnes was 1.25%. The MBC value of fingerroot oil was doubled as the MIC value. The great antibacterial activity of fingerroot essential oil makes it potential to be developed into anti-acne preparations.